Implikasi Putusan Mahkamah Konstitusi Nomor 91/PUU-XVIII Tentang Uji Materi Undang-Undang Nomor 11 Tahun 2020 - Muhammad Alpi Syahrin; Alfikri Alfikri (Program Studi Ilmu Hukum Universitas Maritim Raja Ali Haji, 2022)
After the promulgation of Law Number 11 of 2020 concerning Job Creation, there are still various responses and a judicial review application has even been submitted to the Constitutional Court (MK). Several points in the minutes of the Constitutional Court's decision have legal implications. This paper analyzes the Constitutional Court Decision Number 91/PUU-XVIII concerning the Judicial Review of Law Number 11 of 2020 concerning Job Creation and the executive power of the Constitutional Court against the Judicial Review of Law Number 11 of 2020 concerning Job Creation. The research method in this paper is normative. It is normative because it uses secondary data to examine rules or norms. This research is descriptive in nature so that researchers try to describe the object or present a complete picture of the object or subject under study in accordance with the circumstances as they are with the aim of systematically describing the facts and characteristics of the object or subject being studied appropriately. The results of the discussion show that the Constitutional Court Decision Number 91/PUU-XVIII concerning the Judicial Review of Law Number 11 of 2020 concerning Job Creation has provided legal implications, namely improvements were made within the specified time limit and a prohibition on issuing new implementing regulations related to the Act. -Copyright Act.